Performance of microwave assisted aqueous enzymatic technique for elateriospermum tapos seed oil extraction - Hadi Tan, Nuraimi Azlan (2017)
Green, sustainable and effective extraction method is currently in demand for extraction of valuable compounds from natural resources. In this study, microwave assisted aqueous enzymatic extraction (MAAEE) which uses an electromagnetic wave as heating medium incorporated with non-toxic enzymatic aqueous solution as solvent was applied to extract omega-3 (ω-3) rich oil from Elateriospermum tapos seed. The effect of parameters in the MAAEE process including optimization, oil characterization, and mass transfer models relationship were investigated. In this study, experiments were carried out based on the design of experiment by central composite design using the design expert software. The optimization of extraction was analyzed by the response surface methodology and mass transfer models which were correlated with the models of the modified Fick’s law, Patricelli’s model and mass balance based on broken and intact cells. The results revealed that low microwave power (110 W) and small particle size (0.5 mm) gave significant effect on the extraction yield whereas increasing concentration of enzyme cocktail from 1 to 3% significantly increased the concentration of extracted ω-3 fatty acid. The optimum conditions were determined to be 110 W microwave power, 30 second extraction time, 1% enzyme cocktail concentration and 0.5 mm particle size, resulted in 46.12 ± 1.48% recovery of extraction. Meanwhile, the optimum ω-3 fatty acid concentration was achieved at microwave power of 550 W, extraction time of 75 second, enzyme cocktail concentration of 3% and particle size of 0.5 mm resulted into 348.96 ± 24.88 mg ω-3/g extracted oil compared to 106.57 ± 4.32 mg ω-3/g of oil from Soxhlet extraction. The modeling study indicated mass balance model based on broken and intact cells as the best fitted model which gave the highest value of R2 (0.9932) and lower value of absolute average relative deviation (3.7983) at 550 W of microwave power. Thus, it was proven that MAAEE was able to accelerate the extraction process and provided high quality of ω-3 rich oil extract at the same time.